The family of Pa-di-Amun-neb-nesut-tawy from Thebes (TT 414) revisited The Case Study of Kalutj/Nes-Khonsu (G108 + G137) - Budka, Julia (Archaeopress Publishing, 2022)
"The Family of Pa-di-Amun-neb-nesut-tawy from Thebes (TT 414) revisited provides fresh material about the identity of one of the key figures of the family that reused the Saite tomb of Ankh-Hor (TT 414) in the Asasif from the 4th century BCE onwards. It is the woman Kalutj/Nes-Khonsu, who was previously listed in the genealogical register of TT 414 as Pa-di-Amun-neb-nesut-tawy's daughter and wife of one of his sons, Hor. By examining objects found by the agents of the consuls in the 19th century CE and those found by the Austrian mission in the 1970s in TT 414 and in wider Theban contexts, the authors are able to identify Kalutj/Nes-Khonsu, wife of Hor, as another, until now overlooked individual, separate from his sister with the same name. The examination of the funerary assemblage of Kalutj/Nes-Khonsu and of objects belonging to her husband, daughter and sons reveals not only details of Late Dynastic and Ptolemaic burial customs in Thebes but also additional information on the priesthood of Khonsu and of the sacred baboons in this era. This new identification of a previously overlooked person, the mistress of the house and daughter of the first prophet of Amun, Kalutj/Nes-Khonsu (G108 + G137), demonstrates that the finds from TT 414 are still far from being processed in their totality. This material has the potential to provide answers to some of the open questions regarding Late Dynastic/Ptolemaic Thebes and to contextualise funerary assemblages."